2002
DOI: 10.1074/jbc.m206702200
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in Pro-thyrotropin-releasing Hormone Processing and Abnormalities in Thermoregulation in CpeMice

Abstract: Cpefat/fat mice are obese, diabetic, and infertile. They have a mutation in carboxypeptidase E (CPE), an enzyme that converts prohormone intermediates to bioactive peptides. The Cpe fat mutation leads to rapid degradation of the enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…As an adaptive response to increase body temperature, cold exposure is also associated with increased expression of preproTRH in hypophysiotropic neurons and, in turn, increased secretion of TSH and a subsequent increase in thyroid hormone levels (72). In studies with the Cpe fat mouse, we demonstrated that the Cpe fat mutation might affect TRH biosynthesis and that it caused aberrant proTRH processing (38); this suggests that various products derived from proTRH can be independently regulated under altered physiological conditions. Interestingly, genetically obese (ob/ob) mice exposed to a cold environment showed a low increase in brown adipose tissue thermogenesis, a delayed increase in thyroxine 5′-deiodinase, and a reduced increase in serum T 3 level, and these mice became hypothermic (73,74).…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…As an adaptive response to increase body temperature, cold exposure is also associated with increased expression of preproTRH in hypophysiotropic neurons and, in turn, increased secretion of TSH and a subsequent increase in thyroid hormone levels (72). In studies with the Cpe fat mouse, we demonstrated that the Cpe fat mutation might affect TRH biosynthesis and that it caused aberrant proTRH processing (38); this suggests that various products derived from proTRH can be independently regulated under altered physiological conditions. Interestingly, genetically obese (ob/ob) mice exposed to a cold environment showed a low increase in brown adipose tissue thermogenesis, a delayed increase in thyroxine 5′-deiodinase, and a reduced increase in serum T 3 level, and these mice became hypothermic (73,74).…”
Section: Figurementioning
confidence: 78%
“…The role of CPE has been elucidated in Cpe fat /Cpe fat mice, which lack functional CPE because of a naturally occurring mutation (37). We found that hypothalamic TRH in these mice was depressed by at least 75% compared with that in wild-type controls (38). These mice cannot maintain their body temperatures when exposed to cold due to substantial decrease of hypothalamic TRH and reduction in thyroid hormone.…”
Section: Introductionmentioning
confidence: 84%
“…shown by the presence of unprocessed prohormone intermediates such as prodynorphin intermediates and ␣-melanocyte-stimulating hormone (␣MSH) precursors (Berman et al, 2001), pro-thyrotropin-releasing hormone intermediates (Nillni et al, 2002), procholecystokinin intermediates (Lacourse et al, 1998), and proinsulin and cocain-and amphetamine-related transcript (CART) precursors (Cawley et al, 2004) in Cpe fat mice and CPE-knockout mice. Among these hormones, inefficient production of mature ␣MSH and CART is suggested to enhance food intake and lead to adult-onset obesity in the Cpe fat mouse and CPE-knockout mouse (Zimmermann-Belsing andFeldt-Rasmussen, 2004: Cawley et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1). Extensive research has been done during the last two decades to understand the post-translational processing of proTRH (11)(12)(13), the convertases responsible for pro-TRH cleavage (14 -17) the intracellular sites of proTRH processing (18,19). More recently the importance of the initial cleavage for proTRH sorting (20), and the implications of the C-terminal disulfide bond in this process (21) has been uncovered.…”
mentioning
confidence: 99%